"Cap‐Pair" Effect as the Reason of the Catalytic Properties of Nicotinic Acid: Experimental and Theoretical Studies. Issue 4 (16th November 2022) - Nieszporek, Jolanta
Abstract: The influence of nicotinic acid (NC) on the kinetics and the mechanism of electroreduction of Zn 2+ ions in the acetate buffer (pH=6.0) was investigated using electrochemical methods (EIS, CV, SWV and DC). It was shown that the anions of NC catalyze the electrode reaction (cap‐pair effect) by adsorbing on the surface of the mercury electrode. The catalytic activity of NC is due to its ability to form active NC−Zn 2+ complexes on the electrode surface, facilitating the electron transfer process. However, no evidence of the formation of such complexes in the solution was found using classical molecular dynamics. Moreover, it was proved that the electroreduction of Zn 2+ ions in the presence of NC is a two‐stage process. The first stage involves the transfer of the first electron, preceded by the partial loss of the hydration shell by the Zn 2+ ions and formation of the active complex. Moreover, it was shown that in the range of lower concentrations, c≤1.10 −2 mol.dm −3, the nicotinic acid shows weaker catalytic abilities than another form of vitamin B3 – nicotinamide. In the range of its higher concentrations, the nicotinic acid is a more effective catalyst for the electroreduction of Zn 2+ ions. Abstract : The catalytic effect of nicotinic acid on the electro‐reduction kinetics of Zn 2+ ions can be explained by the formation of active complexes on the electrode surface between the anions of nicotinic acid adsorbed on it and a zinc aquacomplex ("Cap‐Pair" effect).